Sexual rights and religion: Same-sex marriage and lawmakers' catholic identity in Argentina - Vaggione, Juan Marco (2011)
The purpose of this essay is to consider some of the ways in which the sectors of society that strongly identified with religion sought to influence the process of legal reform that culminated in the authorization of marriage for same-sex couples. The essay focuses on the complex influence of Catholicism on the legal debate, given that without a doubt the Catholic Church remains the main challenge to the expansion of sexual rights in Latin America. First, the Catholic Church´s sexual politics will be characterized by considering the main official Vatican documents on the matter. Beyond the fact that the Church´s actions vary in different countries, examining the Vatican´s construction of sexual politics is crucial for understanding the institution´s political participation in opposition to the expansion of sexual rights. The calls for lawmakers, both in the Vatican documents and in the Church hierarchy´s public interventions, are considered. Second, the essay will analyze the interventions of Catholic legislators during the Parliamentary debate in Argentina. Numerous legislators, at the moment of justifying their votes, identified as Catholics despite differing in their positions on marriage for same-sex couples. This essay proposes four types of articulations between religious identity and the role of lawmakers when regulating sexuality. By considering these two levels-the Catholic Church´s sexual politics and the legislator´s articulations-the essay aims to present a complex picture of the connections between religion and politics, which allowed for the legal reform recognizing marriage for same-sex couples.